IMPROVING STUDENT’S SPEAKING SKILL THROUGH GALLERY WALK AT SMK MIFTAHUL HASAN AL-UTSMANI - Afkarina, Nailah; Hatip, Mochammad; Oktarini, Widya (Unversitas Katolik Santo Thomas, 2025)
In English language learning, speaking skill is one of the important basic abilities but often becomes a challenge for students, especially due to limited vocabulary, lack of confidence, and fear of making mistakes. This study aims to determine whether there is an improvement in students' speaking skills through the application of the Gallery Walk method in class X-2 students of SMK Miftahul Hasan Al-Utsmani in the 2024/2025 school year. This study used a qualitative approach with the Classroom Action Research (CAR) method consisting of two cycles. Each cycle includes planning, action, observation, and reflection stages. The subjects in this study were 21 students of class X-2. Data collection techniques used observation, speaking tests, documentation, and assessment rubrics covering aspects of fluency, pronunciation, vocabulary, and content understanding. Based on the results of the cycle 1 test, the average student score of 61.1 shows that there are still many students who have not reached the minimum completion criteria (KKM). However, after improvements were made in cycle 2 in the form of simplifying topics, providing vocabulary lists, and re-explaining instructions, the average score increased to 75.1 and met the KKM. The observation results also showed an increase in students' active participation and confidence in speaking activities. Thus, it can be concluded that the Gallery Walk method has a significant effect on improving students' speaking skills. This method is proven to create a collaborative, interactive learning atmosphere and support the development of speaking skills effectively.